Effect of Improved Trichoderma harzianum on Growth and Resistance Promotion in Bean Plant - Sahar Mahmoodian; Mojegan Kowsari*; Mostafa Motallebi; Mohammadreza Zamani; Zahra Moghaddasi Jahromi (Brazilian Archives of Biology and Technology, 2022)
Abstract Different species of Trichoderma harzianum have been used mainly as an antagonist against a number of plant diseases. There is a direct relationship between the biocontrol potential of these fungi and the rate of enzymatic degradation of the cell walls of pathogens. Following the successful production of chimeric chit 42 via protein engineering in the previous work of authors, the resulting recombinant protein was transferred to T. harzianum. In this study presence and stability of chimeric Chitinase (Chit42-ChBD) was verified then growth stimulating and biocontrol potential of the six improved isolates were evaluated on bean plants under laboratory and greenhouse conditions compared to the wild type. Among engineered isolates, Chit42-ChBD3 with 53.83% growth inhibition on Rhizoctonia showed the highest growth rate and sporulation compared to the wild type in the dual culture test. The results showed that ChBD15 and ChBD13 had better performance in terms of increasing nutrient uptake and root growth thereby enhancing the growth rate and yield performance of the whole plant compared to the plants treated with wild type and non-T. harzianum treated plants.